High Performance Liquid Chromatography Determination of Sertraline in Human: Quantification of sertraline by HPLC - Amir Farshchi,; Golbarg Ghiasi,; Gholamreza Bahrami, (Iranian Journal of Pharmaceutical Sciences, 2009)
An accurate and sensitive reversed-phase high-performance liquid chromatograph-ic method for determination of sertraline in human serum is described using 4-chloro-7-nitrobenzofurazan as pre-column derivatization agent. The drug and aninternal standard (azithrimycin) were extracted from serum using a mixture ofdiethyl ether-chloroform and subjected to the pre-column derivatization with thereagent. Analysis of the resulted derivatives was performed on a Lichrosorb CN(250×4.0 mm) column using a mobile phase composed of methanol and sodium phosphate buffer (0.05 M; pH 3.7) containing 2 ml/lit triethylamine (63:37 v/v).Detector response was monitored at excitation and emission wavelengths of 470 and537 nm, respectively. The calibration curve was linear over the concentration range of 2 to 640 ng/ml. The lower limits of detection and quantification were 0.5 and 2ng/ml, respectively. The validation of the analysis was carried out in terms of specificity, sensitivity, linearity, precision, accuracy and stability. The validated method was shown to be accurate, with intra-day and inter-day accuracy from 0.3 to 4.2%and precise, with intra-day and inter-day precision from 2.4 to 15.5%. The drug is detected at concentrations as low as 2 ng/ml in a 0.5 ml serum sample and the described method can be easily applied in human single-dose pharmacokinetic studies of sertraline.